Finding the Śāṭān in the Sacred: An Exploration of Resignification and Generative Sacredness in The Dying of the Light - Willett, Kit (Auckland University of Technology, 2021)
The Dying of the Light is the story of Paradise Lost (2005), reframed. It tells of Lucifer escaping heaven, an abusive institution and family structure, then living with their trauma, and freeing humanity (or so they think). The text explores themes of ecofeminism, postcolonial and institutional power, and familial abuse. The Exegesis, ‘Finding the Śāṭān in the Sacred’, reflects on the process of writing the creative thesis and examines how specific sacred practices can be used as generative tools for poetry writing.
Keywords: Poetry; Paradise Lost; Sacred practice; Ecofeminism